Proton Therapy Facility Planning From a Clinical and Operational Model. (October 2015) - Das, Indra J.; Moskvin, Vadim P.; Zhao, Qingya; Cheng, Chee-Wai; Johnstone, Peter A.
This paper provides a model for planning a new proton therapy center based on clinical data, referral pattern, beam utilization and technical considerations. The patient-specific data for the depth of targets from skin in each beam angle were reviewed at our center providing megavoltage photon external beam and proton beam therapy respectively. Further, data on insurance providers, disease sites, treatment depths, snout size and the beam angle utilization from the patients treated at our proton facility were collected and analyzed for their utilization and their impact on the facility cost. The most common disease sites treated at our center are head and neck, brain, sarcoma and pediatric malignancies. From this analysis, it is shown that the tumor depth from skin surface has a bimodal distribution (peak at 12 and 26 cm) that has significant impact on the maximum proton energy, requiring the energy in the range of 130-230 MeV. The choice of beam angles also showed a distinct pattern: mainly at 90° and 270°; this indicates that the number of gantries may be minimized. Snout usage data showed that 70% of the patients are treated with 10 cm snouts. The cost of proton beam therapy depends largely on the type of machine, maximum beam energy and the choice of gantry versus fixed beam line. Our study indicates that for a 4-room center, only two gantry rooms could be needed at the present pattern of the patient cohorts, thus significantly reducing the initial capital cost. In the USA, 95% and 100% of patients can be treated with 200 and 230 MeV proton beam respectively. Use of multi-leaf collimators and pencil beam scanning may further reduce the operational cost of the facility.